The Female Vaginal Microbiome in Health and Bacterial Vaginosis - Chen, Xiaodi; Lu, Yune; Chen, Tao; Li, Rongguo (Frontiers in Cellular and Infection Microbiology, 2021)
The vaginal microbiome is an intricate and dynamic microecosystem that constantly undergoes fluctuations during the female menstrual cycle and the woman’s entire life. A healthy vaginal microbiome is dominated by Lactobacillus which produce various antimicrobial compounds. Bacterial vaginosis (BV) is characterized by the loss or sharp decline in the total number of Lactobacillus and a corresponding marked increase in the concentration of anaerobic microbes. BV is a highly prevalent disorder of the vaginal microbiota among women of reproductive age globally. BV is confirmed to be associated with adverse gynecologic and obstetric outcomes, such as sexually transmitted infections, pelvic inflammatory disease, and preterm birth. Gardnerella vaginalis is the most common microorganism identified from BV. It is the predominant microbe in polymicrobial biofilms that could shelter G. vaginalis and other BV-associated microbes from adverse host environments. Many efforts have been made to increase our understanding of the vaginal microbiome in health and BV. Thus, improved novel and accurate diagnosis and therapeutic strategies for BV have been developed. This review covers the features of vaginal microbiome, BV, BV-associated diseases, and various strategies of diagnosis and treatment of BV, with an emphasis on recent research progresses.